Rapid decline in 51Cr-ethylenediaminetetraacetic acid-measured renal function during the first weeks following liver transplantation. (11th January 2019) - Hornum, Mads; Penninga, Luit; Rostved, Andreas A; Christensen, Karl B; Oturai, Peter; Plagborg, Ulla; Feldt-Rasmussen, Bo; Hillingsø, Jens G; Rasmussen, Allan
Abstract: Background: Renal dysfunction is a serious late complication after liver transplantation (LTX), but there are no studies addressing the early changes associated with this complication. Methods: We prospectively studied glomerular filtration rate (GFR) before and at 1, 3 and 12 weeks after LTX using 51 Cr-labelled ethylenediaminetetraacetic acid clearance in 37 adult consecutive patients who underwent non-acute first LTX. Results: The mean (±SD) age was 49.5 ± 9.5 years, and the male:female sex ratio was 21:16. Diagnoses were autoimmune liver diseases (17), alcoholic cirrhosis (10) and other diseases (10). Immunosuppressive treatment consisted predominantly of triple-drug therapy. A total of 27 of the 37 patients were eligible for GFR analysis at all times. The mean (±SD) GFR was 86 ± 26 mL/min/1.73 m 2 before LTX, and 77 ± 30 mL/min/1.73 m 2 at 1 week, 64 ± 27 mL/min/1.73 m 2 at 3 weeks and 64 ± 23 mL/min/1.73 m 2 at 12 weeks after LTX, comparable to a reduction in mean GFR compared with baseline values of 10% (P = 0.1907), 25% (P = 0.0010) and 26% (P = 0.0007). Age and number of blood transfusions during surgery were identified as risk factors for this decline as well as gender, but not pre-transplant diagnosis, model of end-stage liver disease score, cold ischaemia time or post-transplant area under the curve tacrolimus during Days 0–14. Conclusions: Using measured rather than estimated GFR, our results show that severe renal impairment occurs during the first week after LTX. These results emphasize the need for more studies addressing renoprotective treatment strategies.